Clinical features and risk factors of liver injury in patients with Chlamydia psittaci pneumonia- a retrospective analysis - Guo, Xuejing; Zhu, Dan; Chen, Hui (Frontiers in Cellular and Infection Microbiology, 2024)
Background: Research into the effects of Chlamydia psittaci pneumonia on the liver has emerged in the last few years. However, no studies have systematically described liver injury in patients with psittacosis. We present the first report on the clinical features and risk factors of liver injury in patients with Chlamydia psittaci pneumonia.Methods: We retrospectively collected the clinical parameters for 46 patients with Chlamydia psittaci pneumonia admitted to Jinhua Central Hospital from January 2019 to February 2023. We analyzed the liver function parameters and summarized the clinical characteristics and risk factors of liver injury.Results: Among the 46 patients, 39 (84.8%) had abnormal liver function, and 23 (50.0%) had liver injury. The ratio of patients with a history of alcohol consumption (39.1% vs.4.3%, P =0.004) or severe pneumonia (56.5% vs. 26.1%, P =0.036) was higher in the liver injury group compared with the non-liver injury group. Laboratory tests showed higher lactate dehydrogenase (LDH) levels in the liver injury group (P <0.001). The optimal cut-off LDH level associated with liver injury was 473 IU/L as determined by ROC curve analysis. Furthermore, multivariate logistic regression analysis demonstrated that a history of alcohol consumption (odds ratio [OR] = 11.251; 95% confidence interval [CI] = 1.022 ~ 123.897, P =0.048) and an LDH level of ≥ 473IU/L (OR = 11.635, 95% CI = 1.832 ~ 73.869, P =0.009) were independent risk factors for liver injury. Conclusions: A history of alcohol consumption and an LDH level of over 473 IU/L are independent risk factors for Chlamydia psittaci pneumonia-related liver injury. It is recommended that particular attention be given to monitoring and evaluating liver function parameters when treating patients with Chlamydia psittaci pneumonia who have a high LDH level and history of alcohol consumption.